Adolescents' own and parental expectations for cross‐group friendship in the context of societal inequalities. (11th December 2021) - Grütter, Jeanine; Dhakal, Sandesh; Killen, Melanie
Abstract: This study investigated adolescents' expectations about friendships between peers from different socioeconomic status (SES) in Nepal. Overall, Nepalese adolescents ( N = 389, Mage = 14.08; grades: 7–10) attributed more negative intentions to high‐SES than to low‐SES peers and expected that parents of high‐SES targets would disapprove of cross‐group friendships, referencing social hierarchies and reputation. Expectation about parents of low‐SES targets were that they would support cross‐SES friendships, citing moral concerns and social mobility. Thus, adolescents were aware of systemic reasons that underlie SES biases. Given that low‐SES adolescents often suffer when excluded from peer experiences, these findings indicate that ethnic‐racial socialization (ERS) parental strategies could include protecting children from experiences related to SES inequalities and a lack of social mobility as well as experiences of discrimination.